The countryside and the encroaching urban fringe: Housing and suburbanisation: is this nexus now out of control? - Kaltenbrunner, Robert (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
There remains today little in common between the concept underlying the phenomenon we refer to as “the city”, on the one hand, and the actual reality we can observe and experience. One reason for this is the apparently insatiable desire on the part of large groups in society for a home of their own in a leafy environment; for distance from the hectic, noisy, polluted and increasingly hazardous city centre; for greater closeness to nature; for a sense of belonging to a community, which is seen to guarantee greater security, peace and quiet and social homogeneity; for an environment more child-friendly than that found in the inner city. In stark contrast to any discourse on the subject of urbanity — and reaffirmed impressively yet again just recently in both surveys and empirical studies — for many people a home of their own, with garden, is now well established as the very epitome of how they would ideally like to live. And it is this — admittedly among other factors — which generates suburbanisation. Even accepting that sprawling settlement development by no means represents a lack of planning, but is rather the result of conflicting and — over the course of time — mutually neutralising values with regard to what we think cities can and should be; and granting too that every municipality thinks first and foremost — as indeed it is required to — of its own best interests: nonetheless, what we refer to as “urban sprawl” should not simply be stigmatised or accepted as an unalterable fact of life. On the contrary: suburbanisation needs to be seen, to a much greater degree than has previously been the case, as a challenge for urban development, as a sign of a need to envision spatial concepts which take into account both the housing market and individual aspirations with regard to housing.